2009
DOI: 10.1103/physrevd.80.056002
|View full text |Cite
|
Sign up to set email alerts
|

QCD sum rules for theX(3872)as a mixed molecule-charmonium state

Abstract: We use QCD sum rules to test the nature of the meson Xð3872Þ, assumed to be a mixture between charmonium and exotic molecular ½c "q½q " c states with J PC ¼ 1 þþ . We find that there is only a small range for the values of the mixing angle that can provide simultaneously good agreement with the experimental value of the mass and the decay width, and this range is 5 0 13 0 . In this range we get m X ¼ ð3:77 AE 0:18Þ GeV and ÀðX ! J=c þ À Þ ¼ ð9:3 AE 6:9Þ MeV, which are compatible, within the errors, with the ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
165
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(179 citation statements)
references
References 57 publications
12
165
1
1
Order By: Relevance
“…To reproduce the small width of the X(3872), it was considered as a mixture between charmonium and molecular state with J PC = 1 ++ in Ref. [560]. They found a small mixing angle 5 • ≤ θ ≤ 13 • to reproduce the parameters m X = (3.77 ± 0.18) GeV and Γ(X → J/ψπ + π − ) = (9.3 ± 6.9) MeV.…”
Section: Molecular Schemementioning
confidence: 99%
“…To reproduce the small width of the X(3872), it was considered as a mixture between charmonium and molecular state with J PC = 1 ++ in Ref. [560]. They found a small mixing angle 5 • ≤ θ ≤ 13 • to reproduce the parameters m X = (3.77 ± 0.18) GeV and Γ(X → J/ψπ + π − ) = (9.3 ± 6.9) MeV.…”
Section: Molecular Schemementioning
confidence: 99%
“…where Q 2 = −q 2 , and the function H(Q 2 ) represents the contribution of the pole-continuum transitions [15,22,23,24]. The…”
Section: Three-point Correlation Functionmentioning
confidence: 99%
“…Here we study the Y (3940), within QCDSR approach, using a mixed charmoniummolecule current, following the works in Refs. [15,16,17,18] where the states X(3872) and Y (4260) were considered as molecule-charmonium states.…”
Section: Introductionmentioning
confidence: 99%
“…[53] and references therein). In addition, theDΛ c andD * Λ c thresholds are also located just below theD ( * ) Σ may be explained by this admixture picture of a cc core plus higher Fock components due to the coupling to the meson-meson continuum [56,[65][66][67][68][69][70][71][72][73][74][75][76][77][78]. For those interested in X, Y , and Z exotic states, a general review can be found in [56].…”
Section: Introductionmentioning
confidence: 99%